POTENSI DAN TEKNOLOGI PENGOLAHAN KOMODITAS AREN SEBAGAI PRODUK PANGAN DAN NONPANGAN / Potential and Technology Processing of Palm Sugar Commodity As Food and Non-Food Products - Rindengan Barlina; Suzanne Liwu; Engelbert Manaroinsong (Jurnal Penelitian dan Pengembangan Pertanian, 2020)
The area of palm sugar plantations in Indonesia is estimated at 61,924 ha, which is spread over 26 provinces. The area of palm sugar plants increased by an average of 2.0% per year with a production growth rate of 1.9% per year. Generally, the main product expected is the neera (which is tapped from spadix). In its development, other parts of the sugar palm plant began to be glimpsed, because it has an impact on increasing the added value of commodities. This paper aims to express the potential of palm sugar as a source of raw materials for processing various products, especially food products. Like just a coconut plant, the sugar palm plant can also be dubbed the tree of life because all parts can be utilized. Neera as the main product, whose production can reach 8-22 liters/tree/day is the raw material for processing sugar. Besides that it can be processed into palm wine and soft drinks. Palm stems (pith parts) can be processed into starch and production can reach 60-70 kg / tree. Sugar palm starch can substitute flour in the processing of biscuits, MP-ASI, noodles and as raw material for edible films. Whereas the fruit can be processed into the kolang kaling and can be further processed into various products. Food product processing technology from palm sugar is available, so it is expected to increase the variety of food products, while improving consumer health and farmers’ incomes.Keywords: Sugar palm, potential, processing, product AbstrakLuas areal tanaman aren di Indonesia diperkirakan 61.924 ha yang tersebar pada 26 propinsi. Areal tanaman aren bertambah rata-rata 2,0% dengan laju pertumbuhan produksi 1,9% per tahun. Produk utama yang diharapkan dari aren adalah nira yang disadap dari mayang. Dalam perkembangannya, bagian-bagian lain dari tanaman aren mulai dilirik, karena juga memiliki nilai tambah. Naskah ini mengemukakan potensi tanaman aren sebagai sumber bahan baku berbagai produk, terutama pangan. Seperti halnya kelapa, tanaman aren juga dapat dijuluki sebagai tanaman serbaguna karena semua bagian tanaman dapat dimanfaatkan. Nira sebagai produk utama aren memiliki produktivitas antara 8-22 liter/pohon/hari dan merupakan bahan baku gula cetak, gula cair, dan gula semut. Selain itu, nira aren dapat diolah menjadi palm wine dan minuman ringan. Batang aren (bagian empulur) dapat diolah menjadi pati dengan produktivitas 60-70 kg/pohon. Pati aren dapat mensubstitusi tepung terigu dalam pembuatan biskuit, makanan pelengkap air susu ibu, mie, dan bahan baku edible film. Buah aren umumnya diolah menjadi kolang kaling dan dapat diproses lebih lanjut menjadi berbagai produk. Teknologi pengolahan produk pangan dari aren telah tersedia, yang diharapkan dapat menambah keragaman produk pangan, sekaligus meningkatkan kesehatan konsumen dan pendapatan petani.Kata kunci: Aren, potensi, pengolahan, produk